Old cowboys never die - Johnstone, William W.; Johnstone, J. A. (Kensington Publishing Corp., 2022)
When two cattlemen who are near retirement attempt to deliver their last two thousand cows in hopes of one final payday, they must stop their boss's lawyer who is plotting to steal the workers' cash.